2010
DOI: 10.48550/arxiv.1009.0252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-archimedean tame topology and stably dominated types

Abstract: Let V be a quasi-projective algebraic variety over a nonarchimedean valued field. We introduce topological methods into the model theory of valued fields, define an analogue V of the Berkovich analytification V an of V , and deduce several new results on Berkovich spaces from it. In particular we show that V an retracts to a finite simplicial complex and is locally contractible, without any smoothness assumption on V . When V varies in an algebraic family, we show that the homotopy type of V an takes only a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…For instance, while it has been known for some time that the analytification of a smooth variety over a trivially normed field is contractible, the only known proof that they are locally contractible is quite recent and passes through model theory and spaces of stably dominated types. This local contractibility is just one of the fundamental consequences of the tameness theorem of Hrushovski and Loeser [HL12].…”
Section: Tameness Of Analytificationsmentioning
confidence: 86%
See 1 more Smart Citation
“…For instance, while it has been known for some time that the analytification of a smooth variety over a trivially normed field is contractible, the only known proof that they are locally contractible is quite recent and passes through model theory and spaces of stably dominated types. This local contractibility is just one of the fundamental consequences of the tameness theorem of Hrushovski and Loeser [HL12].…”
Section: Tameness Of Analytificationsmentioning
confidence: 86%
“…In particular, the proof of the tameness theorem for a single variety in dimension n requires a tameness statement for families of varieties in lower dimensions. See the Bourbaki notes of Ducros [Duc13] for an excellent introduction to this work, and the original paper [HL12] for further details. 4.4.…”
Section: Tameness Of Analytificationsmentioning
confidence: 99%
“…Given an n-tuple, c, and set A, there are certain points that must be in any closed A-definable set containing c, namely the i-closures defined in this section. The iclosure of c for each i ≤ n is the limit (in the sense of [HL10]) of tp(c ≥Q(i) /Ac <Q(i) ). A principle of our proof of Theorem A will be that if a function can be continuously extended to the i-closure points for all i, then it can be continuously extended to an A-definable closed set containing c. We can assure continuity on i-closures by bounding the various values a function takes by another function that goes to 0 as it approaches an i-closure point.…”
Section: Good Bounds and I-closuresmentioning
confidence: 99%
“…The way that such a set containing a type can fail to exist is that, in some sense, the type lies in a "gap" between two regions on which the function takes very different values, but which share a common boundary point that is the limit of the type, in the sense of [HL10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Berkovich showed that smooth analytic spaces over a field are locally contractible [4,5]. More recently, Payne [26] showed that the analytification of an algebraic variety over a field can be viewed as an inverse limit of finite polyhedral complexes; separately, Hrushovski and Loeser [16] have used model-theoretic techniques to show that such analytifications are locally contractible and retract onto finite CW-complexes. One can also relate homotopy types of analytic spaces to degenerations; for instance, the analytification of a semistable curve over a complete discretely valued field has the same homotopy type as the graph of the special fibre of a minimal proper regular model over the valuation subring.…”
Section: Introductionmentioning
confidence: 99%